Effects of environmental and spatial factors on the distribution of anuran species with aquatic reproduction in central Amazonia - Menin, Marcelo; Waldez, Fabiano; Lima, Albertina Pimental (Herpetological Journal, 2011)
We evaluated the effect of environmental and spatial variables on the distribution of 11 species of anurans in 10,000 ha of nonflooded forest in central Amazonia. Diurnal and nocturnal frog assemblages were sampled in 72 plots using visual and auditory surveys. Distance from stream was the best predictor for species richness and abundance, with an increase in distance resulting in a decrease in number of species and individuals. Three species (Osteocephalus oophagus, Trachycephalus resinifictrix and Vitreorana oyampiensis) were not influenced by environmental predictors and occurred along all environmental gradients. The watersheds did not influence the abundance of the majority of species except Allobates sp., Atelopus spumarius and Leptodactylus rhodomystax. Our results indicate that most species studied occur along the margins of streams, which they also use as dispersal corridors. The removal of forests near streams could lead to local extinctions.